THE DEVELOPMENT OF WEB BASE SOSIOMETRI ANALYSIS APPLICATION IN THE NOMINATIVE TYPE FOR SENIOR HIGH SCHOOL - I Wayan Putra Suyana (Universitas Pendidikan Ganesha, 2013)
Students’ environment is the place near students to interact with other people athough doing activity. Social conditions in the school especially the one student with other students are not always harmony. This casecan give negative effect for the students’ result of the study in the school. Seen the important of harmony social interaction role, so in the school need one method and instrument that organizing of social guidance service is sosiometry. Sosiometry is a method that have function to know the students’ social condition in their class, how much they can be accepted in their environment class, how much they are rejected, how much they are popular or although isolated of students itself. In the school, sociometry is still manually done so it spent so much time. Based on these problems, it is necessary to develop a software that can help students to get counseling services optimally and can significantly assist the counseling teachers in organizing social services using sosiometri. The implementation of the study was developed using the waterfall model of research methods and using php programming language with mysql as database. The software is designed with the ability to create a poll or questionnaire, questionnaire response analysis and converts into a form of tabulation table and graph form preferred direction based on answers to the questionnaire. Such software will be expected to assist in organizing the counseling Teacher performance of social services, especially in the implementation sosiometri test that can be done quickly with an accurate analysis.